Axial compressive behaviour of RC columns strengthened with rectangular steel tube and cementitious grout jackets. (June 2021) - Wang, Fengqin; Wang, Jingfeng; Yang, Hua; Shen, Qihan
Abstract: The welded steel tube and high-strength cementitious grout jacketing is a hybrid strengthening method for deficient reinforced concrete (RC) column without enlarging its entire cross-sectional area. This paper presents an experimental study on the performance of the welded steel tube and cementitious grout jacketing retrofitted RC (STGRRC) stub column under axial compression to figure out its strengthening effect. A total of eight STGRRC stub columns and one high-strength cementitious grout jacketing strengthened RC stub column are designed and analysed to investigate the effects of various parameters including the aspect ratio, the concrete cross-sectional area ratio ( A c / A ) and the concrete strength. To better acknowledge the strengthening feature of the type of composite column, detailed discussions on the crucial indexes in terms of the confinement effect, the strength enhancement and the damage failure analysis are presented. The result reveals that the strength, stiffness and ductility of the original RC column could be highly improved by using this strengthening method. The axial compressive resistance of STGRRC stub column decreases with the increasing of aspect ratio and concrete cross-sectional area ratio. The ductility index value reduces with varying the aspect ratio and concrete strength in ascending order as well as the decreasing of concrete cross-sectional area ratio. To provide a basis for the future design and application, a simplified analysis method is proposed to predict the axial compressive resistance of the STGRRC stub column based on the limit equilibrium theory and verified well with experimental results.